Psychotherapeutic Treatment for Anorexia Nervosa: A Systematic Review and Network Meta-Analysis - Zeeck, Almut; Herpertz-Dahlmann, Beate; Friederich, Hans-Christoph; Brockmeyer, Timo; Resmark, Gaby; Hagenah, Ulrich; Ehrlich, Stefan; Cuntz, Ulrich; Zipfel, Stephan; Hartmann, Armin (Frontiers in Psychiatry, 2018)
Background The aim of the study was a systematic review of studies evaluating psychotherapeutic treatment approaches in anorexia nervosa and to compare their efficacy. Weight gain was chosen as the primary outcome criterion. We also aimed to compare treatment effects according to service level (inpatient vs. outpatient) and age group (adolescents vs. adults). Methods The data bases PubMed, Cochrane Library, Web of Science, Cinahl and PsychInfo were used for a systematic literature search (until Feb 2017). Search terms were adapted for data base, combining versions of the search terms anorexia, treat*/therap* and controlled trial. Studies were selected using pre-defined in- and exclusion criteria. Data were extracted by two independent coders using piloted forms. Network-meta-analyses were conducted on all RCTs. For a comparison of service levels and age groups, standard mean change (SMC) statistics were used and naturalistic, nonrandomized studies included. Results Eighteen RCTs (trials on adults: 622 participants; trials on adolescents: 625 participants) were included in the network meta-analysis. SMC analyses were conducted with 38 studies (1,164 participants). While family-based approaches dominate interventions for adolescents, individual psychotherapy dominates in adults. There was no superiority of a specific approach. Weight gains were more rapid in adolescents and inpatient treatment. Conclusions Several specialized psychotherapeutic interventions have been developed and can be recommended for AN. However, adult and adolescent patients should be distinguished, as groups differ in terms of treatment approaches considered suitable as well as treatment response. Future trials should replicate previous findings and be multi-center trials with large sample sizes to allow for subgroup analyses. Patient assessment should include variables that can be considered relevant moderators of treatment outcome. It is desirable to explore adaptive treatment strategies for subgroups of patients with AN. Identifying and addressing maintaining factors in AN remains a major challenge.